Distress in the Nigerian financial services industry: a CBN/NDIC collaborative study - Central Bank of Nigeria (CBN).; Nigerian Deposit Insurance Corporation (NDIC). (Lagos: Central Bank of Nigeria, 1996)
This is a report of a comprehensive review of developments in financial services industry in Nigeria, particularly during the period 1986-1994.
lje 14/3/19
Arch.
Keywords: Financial services; Economic conditions; Economic history; Nigeria